2020
DOI: 10.1108/heswbl-10-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

The skill of discipline – measuring F.I.R.S.T discipline principles in higher education

Abstract: PurposeHuman capital theory suggests that any increase in skills translates into greater productivity of the workforce. Non-cognitive skills, in particular, play a critical role in many domains in life. The aim of this study is to gain a greater understanding of one such skill, discipline. Viewing discipline as a tool for enhancing learning, personal development and increasing overall achievement, this study offers an alternative way to measure discipline in higher education.Design/methodology/approachThis pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Discipline Our study utilised a survey developed for measuring personal discipline in the university sector [ 84 ], underpinned by theoretical principles with the potential to impact the discipline of university students, such as self-determination [ 85 ] or self-efficacy [ 86 ]. Additional questions were asked about the importance that discipline played in both their primary and secondary education: Discipline was an important aspect in my primary school, Discipline was an important aspect in my secondary school .…”
Section: Methodsmentioning
confidence: 99%
“…Discipline Our study utilised a survey developed for measuring personal discipline in the university sector [ 84 ], underpinned by theoretical principles with the potential to impact the discipline of university students, such as self-determination [ 85 ] or self-efficacy [ 86 ]. Additional questions were asked about the importance that discipline played in both their primary and secondary education: Discipline was an important aspect in my primary school, Discipline was an important aspect in my secondary school .…”
Section: Methodsmentioning
confidence: 99%
“…It is less clear how culture and discipline affect college students' learning performance. Although Krskova et al (2020b) have confirmed the construct of internally driven discipline from five dimensions (i.e. focus, intention, responsibility, structure and time management), their approach speaks about how college students self-regulate their learning.…”
Section: Contribution To the Cdc Frameworkmentioning
confidence: 99%
“…A study showed that the extent of effort college students put into coursework and the degree to which they see themselves as hardworking and conscientious predict their academic performance (Robbins et al, 2006). Krskova et al (2020b) have proposed, and later confirmed, the F.I.R.S.T model to demonstrate dimensions of college students' internally driven discipline, which underpins concepts such as selfdetermination, goal-setting, self-regulation and time management. These concepts are in agreement with the self-directed learning (SDL) approach.…”
Section: Introductionmentioning
confidence: 98%
“…Pertinent skills include time management, leadership, teamwork, organisation, communication, critical thinking and problem-solving within pressurised situations (GradIreland, 2018;Azevedo et al, 2012). Such skills are considered significant sources of competitive advantage in today's job market (Krskova et al, 2021), as graduates must keep pace with increasing employer demands for the modern practice of marketing (McQuillan et al, 2021). Through a variety of practitionerinformed experiential learning activities in IMC, students are challenged to not only advance their academic knowledge, but to craft their tacit knowledge and hone their skills and capabilities in order to enrich their work-readiness.…”
Section: Challengementioning
confidence: 99%
“…, 2012). Such skills are considered significant sources of competitive advantage in today's job market (Krskova et al. , 2021), as graduates must keep pace with increasing employer demands for the modern practice of marketing (McQuillan et al.…”
Section: Imc As a Study Contextmentioning
confidence: 99%